National Athletic Trainers' Association position statement: Safe weight loss and maintenance practices in sport and exercise - Turocy, P. S.; DePalma, B. F.; Horswill, C. A.; Laquale, K. M.; Martin, T. J.; Perry, A. C.; Somova, M. J.; Utter, A. C. (Journal of Athletic Training, 2011)
Objective: To present athletic trainers with recommendations for safe weight loss and weight maintenance practices for athletes and active clients and to provide athletes, clients, coaches, and parents with safe guidelines that will allow athletes and clients to achieve and maintain weight and body composition goals.